Orbicularis oris muscle reconstruction and cheiloplasty with Z-plasty in a patient with a transverse facial cleft - Sung-Hyuk Koh; Yeon-Woo Jeong; Jeong Joon Han; Seunggon Jung; Min-Suk Kook; Hee-Kyun Oh; Hong-Ju Park (SpringerOpen, 2019)
Abstract Background Transverse facial clefts are Tessier's number 7 facial cleft among numbers 1-15 in Tessier's classification of craniofacial malformations, which varies from a simple widening oral commissure to a complete fissure extending towards the external ear. Case presentation In a patient with a transverse facial cleft, to functionally arrange the orbicularis oris muscle and form the oral commissure naturally, we performed a surgical procedure including orbicularis oris muscle reconstruction and cheiloplasty with Z-plasty. Conclusion We achieved good results functionally and esthetically by orbicularis oris muscle reconstruction and cheiloplasty with Z-plasty. The surgical modality of our anatomical repair and 3 months follow-up results are presented.